PENGEMBANGAN MEDIA PEMBELAJARAN KOSAKATA BAHASA JEPANG TINGKAT DASAR BERBASIS ANDROID - Tamara Yetsuba; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to create and develop basic Japanese vocabulary learning media that can be used for independent learning. The learning media combines various kinds of design objects, namely text, images, animations, audio, video, and interactive buttons. Besides, the study also aims to determine the feasibility of this learning media. The study was conducted in the XI IPS Class of SMA Negeri 4 Pekanbaru and the XI IPS Class of SMA Negeri 9 Pekanbaru. This research was carried out by employing the ADDIE approach. The research object is learning media in the form of android applications. The research phases include (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. A questionnaire was used as a data collection technique that is analyzed descriptively. The study population consists of all students in the XI IPS Class of SMA Negeri 4 Pekanbaru and the XI IPS Class of SMA Negeri 9 Pekanbaru for the 2021-2022 academic year, with a sample of 25 students from each school. The study resulted in a learning media in the form of an android-based application for Japanese language learning. The assessment scores of feasibilities indicated that: (1) assessment of the material expert was “4.81” with very feasible category, (2) assessment of the media expert was “4” with feasible category, and (3) assessment of the response of students was “4.26” with a percentage of “86.1%”; hence it can be categorized as feasible. This study was conducted using a limited size sample. Conclusion: Android-based learning media for basic Japanese vocabulary is feasible to use in independent learning with some suggestions for future studies.Key Words : Japanese language learning Media, android based application.